Association of the Scottish inflammatory prognostic score with treatment-related adverse events and prognosis in esophageal cancer receiving neoadjuvant immunochemotherapy - Zhao, Qiang; Wang, Liang; Yang, Xun; Feng, Jifeng; Chen, Qixun (Frontiers in Immunology, 2024)
Background To investigate the relationship between the Scottish inflammatory prognostic score (SIPS), treatment-related adverse events (TRAEs), and prognostication in patients with neoadjuvant immunochemotherapy (NICT) for esophageal squamous cell carcinoma (ESCC). Methods A retrospective investigation was carried out on 208 ESCC patients treated with NICT. The relationships between the SIPS, TRAEs, and prognosis [disease-free survival (DFS) and overall survival (OS)] were analyzed. Results The patients, comprising 62 (29.8%) cases of SIPS0, 103 (49.5%) cases of SIPS1, and 43 (20.7%) cases of SIPS2, were categorized into three groups based on SIPS. Among patients with SIPS2, the oldest age (P=0.006), lowest BMI (P=0.001), longest tumor length (P=0.001), most advanced ypT stage (P=0.014), and ypN stage (P<0.001) were identified. Pathological complete response (PCR) rates showed statistically significant variations between the three groups (SIPS0: 45.2%, SIPS1: 27.2%, SIPS2: 16.3%, P=0.004). All TRAEs were found in 63.9% (133 cases) of the cases, with serious TRAEs (grade 3-4) accounting for 13.9% (29 cases). TRAEs themselves were not linked with SIPS (P=0.668), while serious TRAEs had a significant correlation with SIPS (P=0.002). Multivariate logistic analysis showed that SIPS2 seemed to confer serious TRAEs [odds radio (OR)=4.044; 95% CI: 1.395-11.722; P=0.010]. For patients classified as SIPS0, 1, or 2, the 3-year DFS was 83.9%, 58.3%, and 39.5% (P<0.001). The 3-year OS for those with SIPS0, 1, or 2 was 88.7%, 72.8%, and 53.5%, respectively (P<0.001). SIPS was substantially correlated with DFS (but not with OS) and could be utilized as an independent predictor [SIPS2: hazard ratio (HR)=3.743, 95% CI: 1.770-7.914, P=0.001; SIPS1: HR=2.303, 95% CI: 1.149-4.616, P=0.019]. Conclusion The SIPS is associated with serious TRAEs and can be used as a predictor of serious TRAEs in ESCC receiving NICT. SIPS may be employed for pretreatment assessment since it was found to be substantially correlated with DFS.